Corrosion initiation and its effect on bond characteristics and service life of reinforced concrete systems with Cement-Polymer-Composite coated steel rebars. (October 2022) - Kamde, Deepak K.; Pillai, Radhakrishna G.
Abstract: This paper investigates the corrosion and bond characteristics of steel reinforcement with Cement-Polymer-Composite (CPC) coating, which is widely used worldwide to prolong the initiation of corrosion. CPC coating is supposed to be applied on sandblasted or cleaned surface to exploit its full potential. However, CPC coating is generally applied on the rusted or uncleaned surface, which can lead to premature corrosion initiation and associated degradation of the bond between coated steel and concrete. For corrosion studies, 20 lollipop specimens with as-received and sandblasted steels, and with and without CPC coating were cast. These were exposed to chlorides and tested using a recently developed test method based on the linear polarization resistance technique. It was found that as-received, CPC coated steels had 50% less chloride threshold than sandblasted, CPC coated steel. For bond studies, 16 pull-out specimens with CPC coated steel rebars were cast. It was found that even negligible corrosion can lead to ≈50 to 70% reduction in bond strength. This indicates that the corrosion propagation period in the case of CPC coated rebar systems would be negligible. Based on the corrosion and bond results, a new service life model for RC systems with CPC coated steel rebars is proposed. The results highlight that if preventive maintenance is not employed, many structures with CPC coated rebars can experience premature corrosion initiation and significant bond reduction.